Deciding to commit crime in adolescence: do moral beliefs matter? - Timmer, Anastasiia (Journal of crime and justice, 2024)
Recent research has underscored the importance of thoughtful and reflective decision-making (TRDM) abilities of youth in preventing and reducing crime and delinquency. Yet, little attention has been paid to the conditions under which TRDM is more or less likely to have these preventative effects. We draw on data recently collected from adolescents attending schools in three metropolitan US areas (2014–2017) to better understand the role of decision-making in youth crime. This is the first study to assess how TRDM interacts with important developmental factors such as moral beliefs to shape projected crime and delinquency, including violence, property crime, and cyberdeviance. Negative binomial regression models reveal that the crime protective influence of the ability to make thoughtful and reflective decisions is most pronounced among adolescents with stronger moral beliefs. In fact, stronger moral beliefs increase the influence of TRDM on various types of crime and delinquency. We provide suggestions for crime prevention policies and programs focused on fostering deliberative thinking and strengthening the distinction between ‘right’ and ‘wrong’ among adolescents.